2002
DOI: 10.1002/app.10744
|View full text |Cite
|
Sign up to set email alerts
|

The use of polymers as sequestering agents for toxic metal ions

Abstract: Polymer-metal complexes were formed by nonsolvent precipitation technique for the metals Co, Pb, Ni, Cr, and Fe, and polystyrene (Pst), Poly(vinyl chloride) (PVC), and Nylon 66. By means of Fourier transform Infrared studies, it was established that chemical bonds actually do exist between the metal ions and the polymers (i.e., that the metal ions are not simply adsorbed on the surface of the polymers). It was observed also that the degrees of metal-polymer interaction vary from polymer, from metal ion to meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…For the last 7 years, a new material has been employed for SPE: minicolumns packed with poly (vinyl chloride) (PVC) (Su, Lee, & Sun, 2012;Su, Li, & Sun 2008). This sorbent exhibit: (i) high distribution coefficients for the analytes, but not for the possible salt from matrix, (ii) appropriate capacity, and (iii) fast kinetics of sorption and elution (Eboatu, Diete-Spiff, Ezenweke, & Omalu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For the last 7 years, a new material has been employed for SPE: minicolumns packed with poly (vinyl chloride) (PVC) (Su, Lee, & Sun, 2012;Su, Li, & Sun 2008). This sorbent exhibit: (i) high distribution coefficients for the analytes, but not for the possible salt from matrix, (ii) appropriate capacity, and (iii) fast kinetics of sorption and elution (Eboatu, Diete-Spiff, Ezenweke, & Omalu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For online separation of trace elements from microdialysate samples, it is essential that the sorbent exhibit (i) high distribution coefficients for the analytes, but not for the salt matrix, (ii) appropriate capacity, and (iii) fast kinetics of sorption and elution. Recently, Eboatu et al employed pure poly(vinyl chloride) (PVC) as a sorbent to separate transition metal ions from aqueous solutions by means of Lewis acid/base interactions. Meanwhile, Watts et al reported that the adsorption efficiency of sodium ions is extremely low on PVC because it behaves as an acidic polymer.…”
mentioning
confidence: 99%
“…For instance, gels made with or thanks to metal ions have been largely studied [16][17][18][19] but also simple bulk polymers interacting with various metallic cations. [20][21][22] This was particularly developed with ionic polymers for membrane filtration. [23,24] Thermotropic [25][26][27] or lyotropic [28][29][30] liquid crystals have been also based on metal ions or complexes.…”
Section: The Various Hpic Systemsmentioning
confidence: 99%